Non-Small Cell Lung Cancer: Screening, Diagnosis, and Staging - Ferreira, J. (2012)
Lung cancer is the leading cause of cancer deaths worldwide. Tobacco consumption is the primary cause of lung cancer, accounting for more than 85% 90% of all lung cancer deaths. Non-small cell lung cancer accounts for about 85% of all lung cancers. Several studies have shown that low-dose helical CT of the lung detects more nodules and lung cancers, including early-stage cancers, than does chest radiography. The National Lung Cancer Screening Trial results show that three annual rounds of low-dose CT screening reduce mortality from lung cancer. Despite the great debate around lung cancer screening, recently the National Comprehensive Cancer Network has come out in favor of lung cancer screening in an updated set of guidelines. All patients who present with suspect lung cancer should have a complete and meticulous history and physical examination performed to identify symptoms or physical findings suggestive of locally extensive or metastatic disease, assess pulmonary health status, identify significant comorbidities, and assess overall health status. Tissue sampling is required to confirm a diagnosis in all patients with suspected lung cancer. Non-surgical approaches, surgical approaches, or both may be used to obtain a tissue sample. Evaluation of the mediastinal lymph nodes is a key step in the further staging of the patient. The best way of evaluating mediastinal lymph nodes is still a matter of debate. The tumor node metastasis (TNM) International Staging System provides useful prognostic information and is used to stage all patients with non-small cell lung cancer. Recent trials added new data on screening and diagnostic approach. Those data will be reviewed in this paper.